2012
DOI: 10.1634/theoncologist.2011-0465
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Biomarkers of Single-Agent Bevacizumab Therapy in Patients with Advanced Hepatocellular Carcinoma

Abstract: Objective. Hepatocellular carcinoma (HCC) is a highly vascularized tumor in which neoangiogenesis contributes to growth and metastasis. We assessed the safety, efficacy, and potential biomarkers of activity of bevacizumab in patients with advanced HCC.Methods. In this phase II trial, eligible patients received bevacizumab, 5 mg/kg or 10 mg/kg every 2 weeks. The disease-control rate at 16 weeks (16W-DCR) was the primary endpoint. Circulating endothelial cells (CECs) and plasma cytokines and angiogenic factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 53 publications
8
83
1
1
Order By: Relevance
“…Prospective single arm phase Ⅱ Sunitinib Decease Better TTP Boige et al [98] CEC 36 Prospective single arm phase Ⅱ Bevacizumab Early increase Better OR CEC level was not associated with prognosis in this study.…”
Section: No Predictive Valuementioning
confidence: 52%
See 1 more Smart Citation
“…Prospective single arm phase Ⅱ Sunitinib Decease Better TTP Boige et al [98] CEC 36 Prospective single arm phase Ⅱ Bevacizumab Early increase Better OR CEC level was not associated with prognosis in this study.…”
Section: No Predictive Valuementioning
confidence: 52%
“…In the SHARP trial, the increase of VEGF-A plasma concentration during sorafenib treatment observed in patients with advanced HCC did not predict OS or tumor response [63] . Similarly, no association between VEGF-A plasma level changes and outcome was observed in patients treated with bevacizumab for advanced HCC [98] . Accordingly, the VEGF-A could serve as a pharmacodynamic marker of exposure to antiangiogenic agents but did not have prognostic or predictive value [85] .…”
Section: Sorafenib Vs Placebomentioning
confidence: 93%
“…When treated with bevacizumab plus a chemotherapeutic regimen, a better outcome was reported for metastatic colorectal cancer (mCRC) patients with a signature that included lower than average baseline IL6 serum levels (44), whereas in another study of mCRC, a worse outcome was associated with a signature that included lower than average IL6 serum levels (45). High baseline IL6 levels were also reported to predict shorter progression-free survival (PFS) and overall survival (OS) in patients with advanced hepatocellular carcinomas (46). In line with these later studies, we observed in an ovarian cancer trial that aflibercept-treated patients with high IL6 had poorer survival than patients with low IL6 serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…ORR was 13% and 14% interestingly, but this drug failed to develop because of safety concerns. 133,134 Ramucirumab. It is a human IgG1 monoclonal antibody.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%